Dyeing ability and antibacterial activity of cotton with a bacterial prodigiosin extracted from Serratia Marcescens - DR. D.GEETHARAMANI; KRITHIKA.K (International Journal of Pharma and Bio Sciences, 2018)
Prodigiosin, a bacterial pigment is extensively studied in this research to investigate its dyeing and antibacterial potential for the development of antimicrobial medical textiles. Pigmented strains of Serratia marcescens were isolated and mass cultured for the extraction of prodigiosin. The crude extracts were analyzed by HPLC and compared to chemically synthesized prodigiosin. Crude prodigiosin extracts were finished onto woven cotton fabric with two mordants (citric acid and alum) using a standard immersion coating method at three different concentrations (1mg/ml, 2mg/ml and 5mg/ml). Colorimetric data of prodigiosin dyed cotton fabrics were determined by AATCC 135-1985 (2003). Antibacterial activity of the pigment finished fabrics was tested using standard AATCC test methods. The biocompatible properties of the finished fabric were tested using a standard Hen’s egg test - chorio-allantoic membrane (HET-CAM test). The K/S values for Alum finished fabric (5mg/ml prodigiosin) were 12.5 and the K/s values for citric acid finished fabric (5mg/ml prodigiosin) were 13.7. The fabric finished with 5mg/ml prodigiosin exhibited maximum inhibitory zones of 33mm and 31mm against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 6538 respectively. Quantitative antibacterial test exhibited 98% and 95% bacterial reduction against two test organisms. During the HET-CAM test, the prodigiosin finished fabrics does not develop any irritant end points, indicating the biocompatibility of bacterial pigments. The application of prodigiosin in medical textile industries will be thus considered as a suitable replacement for many other synthetic textile dyes; due to their significant characteristics like eco-friendly, antibacterial and biocompatibility.